Hell under fire: modern scholarship reinvents eternal punishment - Morgan, Christopher W.; Peterson, Robert A. (Zondervan, 2004)
This book provides a biblical, systematic, and practical theology of hell. The contributors to this volume unite in affirming the historic Christian doctrine regarding the final destiny of the unsaved: They will suffer everlasting conscious punishment away from the joyous presence of God.